Prognozowanie aktywności zawodowej - Balcerowicz-Szkutnik, Maria (Forecasting of Working Activity, 2006)
The article is devoted to the analysis of the working activity issue, evaluation of its present condition and forecasting of its expected level in the future. The basis of these analyses are time chains for years 1992-2004, derived from BAEL researches and registration data from NSP 2002 register. The evaluation of working activity present level and forecasts of its expected condition were carried out for Poland. The evaluation of labour potential and of the expected level of this potential for years up to 2003 was carried out in the world scale, on the basis of the latest population projections prepared by releveant ONZ research units. The prepared forecasts seem to be important in the activity of any economic unit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 135-144